(untitled) (Foro de Educacion, 2026)
English reading proficiency is a gatekeeping competence in Chinese higher education, yet many college EFL learners experience reading as both cognitively demanding and emotionally threatening. This study examines the interplay between English reading motivation and English reading anxiety and tests whether reading anxiety statistically mediates the association between motivation and English reading performance. Survey data were collected from Chinese university EFL learners (N=300). Reading motivation and reading anxiety were modelled as latent constructs measured by multi-item Likert indicators, and reading performance was operationalized as a scored reading assessment. Structural equation modeling with robust estimation was used to validate measurement quality and estimate direct and indirect pathways while controlling for gender, English proficiency, and reading exposure. Results show that higher reading motivation is associated with lower reading anxiety (standardized β ≈ −0.55), and higher reading anxiety is associated with lower reading performance (β ≈ −0.30). Mediation analysis indicates partial mediation: the indirect pathway through anxiety accounts for approximately one-third of the overall motivation–performance association (≈32%). Robustness checks across gender subgroups and alternative motivation specifications preserve the substantive interpretation of the findings. The study contributes to education-focused EFL reading research by clarifying a motivational–affective mechanism relevant to university literacy development and by highlighting the value of integrating motivation-building designs with anxiety-sensitive reading supports in higher education.